Ludic Populism and Its Unpopular Subversion - Sascha Pöhlmann (European Journal of American Studies)
The commendable critical tendency to increasingly consider the politics of video games in general is routinely met with resistance on the part of those who insist on their apolitical nature, in parallel to other areas of popular culture. In this contested discourse, it is all the more important to be specific about what it actually means to claim that video games are political, and this essay offers one particular way in which to address this issue. Understanding the political as a way of imagining a community as a political actor through symbolic practices, either in the interest of creating the sovereign of democratic systems or an ethnicity, I argue that video games may employ a populist imagination in constructing ‘the people’ as a basically unified group (usually in implicitly or explicitly essentialist ways) as much as they may resist or subvert this populist fantasy of homogeneity. I am especially interested in games that dialectically combine both these aspects at the same time by way of dissonances between their representational elements and their gameplay. Focusing on strategy games and action games, my examples include Civilization V, Democracy 3, Tropico 4, BioShock Infinite, Just Cause 3, and Far Cry 4.